2018
DOI: 10.1093/ecco-jcc/jjy184
|View full text |Cite
|
Sign up to set email alerts
|

Defining Faecal Calprotectin Thresholds as a Surrogate for Endoscopic and Histological Disease Activity in Ulcerative Colitis—a Prospective Analysis

Abstract: BackgroundFaecal calprotectin (FCal) levels are used as a surrogate marker for mucosal inflammation, but thresholds for defining endoscopic or histological disease activity in ulcerative colitis UC) remain unclear. MethodsUsing validated indices, prospective measurements of FCal, symptoms (Simple Colitis Clinical Activity Index, SCCAI), endoscopic (Ulcerative Colitis Endoscopic Index of Severity, UCEIS) and histological activity (Nancy index) were made over 6 months in patients enrolled into the TrueColours UC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
57
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(62 citation statements)
references
References 50 publications
4
57
0
1
Order By: Relevance
“…It ranged from 72 to 250 μg/g, suggesting that patients with FC values above the threshold had a higher rate of microscopic activity of disease. The study of Walsh et al showed that a cut‐off threshold >72 μg/g had a SE of 100% and a PPV of 100% to detect microscopic inflammation. The high rate of SP and NPV was reached in the study of Magro et al with a cut‐off level >100 μg/g (100% for both the values).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It ranged from 72 to 250 μg/g, suggesting that patients with FC values above the threshold had a higher rate of microscopic activity of disease. The study of Walsh et al showed that a cut‐off threshold >72 μg/g had a SE of 100% and a PPV of 100% to detect microscopic inflammation. The high rate of SP and NPV was reached in the study of Magro et al with a cut‐off level >100 μg/g (100% for both the values).…”
Section: Resultsmentioning
confidence: 99%
“…Finally, 12 studies met the inclusion criteria and were included in the review. [13][14][15][25][26][27][28][29][30][31][32][33] The reviewers fully agreed on the selection of eligible articles. Three retrospective cohort studies [29][30][31] and nine prospective cohort studies [13][14][15][25][26][27][28]32,33 were investigated.…”
Section: Search Results and Study Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…Calprotectin is released by granulocyte activation and elevated level of fecal calprotectin (FC) is found in the GI tract inflammation that closely related to inflammatory bowel disease (IBD) activity . Increasing evidence indicates that FC can be used as a noninvasive marker for intestinal/colonic inflammation that helps clinicians distinguish organic inflammatory bowel disease (IBD) from functional irritable bowel syndrome (IBS) . Markers of systemic inflammation, such as C‐reactive protein (CRP) and white blood cells count, have low specificity and sensitivity for IBD, while the gold standard of ileo‐colonoscopy is invasive and expensive .…”
Section: Introductionmentioning
confidence: 99%
“…2,3 Increasing evidence indicates that FC can be used as a noninvasive marker for intestinal/colonic inflammation that helps clinicians distinguish organic inflammatory bowel disease (IBD) from functional irritable bowel syndrome (IBS). [4][5][6] Markers of systemic inflammation, such as C-reactive protein (CRP) and white blood cells count, have low specificity and sensitivity for IBD, while the gold standard of ileo-colonoscopy is invasive and expensive. 3 Thus, noninvasive method for monitoring disease activity is preferable.…”
Section: Introductionmentioning
confidence: 99%